Small-molecule inhibitors of kinases in breast cancer therapy: recent advances, opportunities, and challenges - Bansal, Isha; Pandey, Amit Kumar; Ruwali, Munindra (Frontiers in Pharmacology, 2023)
Breast cancer is the most common malignancy in women worldwide and despite significant advancements in detection, treatment, and management of cancer, it is still the leading cause of malignancy related deaths in women. Understanding the fundamental biology of breast cancer and creating fresh diagnostic and therapeutic strategies have gained renewed focus in recent studies. In the onset and spread of breast cancer, a group of enzymes known as kinases are extremely important. Small-molecule kinase inhibitors have become a promising class of medications for the treatment of breast cancer owing to their capacity to specifically target kinases involved in the growth and progression of cancer. The creation of targeted treatments that block these kinases and the signalling pathways that they activate has completely changed how breast cancer is treated. Many of these targeted treatments have been approved for the treatment of breast cancer as clinical trials have demonstrated their great efficacy. CDK4/6 inhibitors, like palbociclib, abemaciclib, and ribociclib, EGFR inhibitors such as gefitinib and erlotinib and HER2-targeting small-molecule kinases like neratinib and tucatinib are some examples that have shown potential in treating breast cancer. Yet, there are still difficulties in the development of targeted medicines for breast cancer, such as figuring out which patient subgroups may benefit from these therapies and dealing with drug resistance problems. Notwithstanding these difficulties, kinase-targeted treatments for breast cancer still have a lot of potential. The development of tailored medicines will continue to be fuelled by the identification of novel targets and biomarkers for breast cancer thanks as a result of to advancements in genomic and proteomic technology.